The Impact of Digital Sharing Platforms on Supply Chain Management: Efficiency, cost reduction, and market responsiveness - Yang Xu (SHS Web of Conferences)
This study discussed the construction of a digital sharing platform in the field of supply chain management (SCM) and its multi-dimensional and far-reaching impact on performance. With the rapid development of global economic integration and information technology, enterprise SCM is facing unprecedented complexity and challenges. As an innovative solution, the digital sharing platform reshapes the operation mode of the supply chain (SC) and greatly improves efficiency, enhances collaboration, and lays a solid foundation for enterprises to maintain an advantageous position in the fierce market competition. This study defined the concept of a digital sharing platform, expounded its core functions in detail, and analyzed the specific mechanism of the platform in promoting seamless information sharing, optimizing resource allocation, reducing operating costs, accelerating response speed, and improving supplier satisfaction. Through theoretical discussion and empirical analysis, this study concludes that the digital sharing platform is the key driving force to improve the overall performance of the SC and has great strategic significance for sustainable development.